The Importance of Penetration Testing: Design and Specification of an Online Penetration Testing Platform - Alkhatib, Obaida (My University, 2022)
Developing more systems and applications is one of the results of the rapid growth of technology. However, the development process seems to be more complex nowadays in terms of providing a secure environment for vendors and users. The cyber threats are growing and on the other hand, companies are in challenge to ensure the security of their web applications, and software consistently. To help organizations identify their cyber security gaps, they can use penetration testing techniques to identify vulnerabilities in their web applications. Manual security testing could consume more time and managing several products without the use of an automated solution could lead to a mess and miss the tracking of testing and development at the right time. As a result, the alternative efficient method is to use a platform to manage the penetration testing process with the help of automation. This thesis aimed to explain the importance of penetration testing. Also, a study has been conducted and led to the design of an Online Penetration Testing Platform (OPTP) that can be used with a Graphical User Interface (GUI). OPTP could save time in the testing process since a tester will have a variety of online web tests integrated with the platform. The methods used to prepare this thesis are mainly theoretical sources plus designing tools for the platform-related designs. The solution is ready to be implemented. The main goal of proposing the approach is to provide security testers with a tool to manage the discovered vulnerabilities, have a centralized platform to create alerts, apply penetration testing, and have smooth communication with the developers. Cyber security attacks are becoming a major issue in companies. As a result, penetration testing has become needed to assess security, and prevent cyber attackers from gaining access to systems.
Keywords: penetration testing, automation, vulnerability management, online platform